An analysis of third sector sport organisations in an era of 'super-austerity'. Issue 1 (2nd January 2018) - Walker, Catherine M; Hayton, John W.
ABSTRACT: This article investigates the impacts of 'super-austerity' upon sport-focussed third-sector sport organisations (TSSOs) in England and how they negotiate the implications of an increasingly constrained fiscal climate. Set against the backdrop of the recent election of the Conservative government (in 2015), the research explores the relationship of these TSSOs to both local and central government. To do this, the authors draw upon semi-structured interviews undertaken with the chief executive officers/managers of 14 TSSOs of varying size and scope. The article reports how TSSOs have acted to negotiate the advances of 'super-austerity' and move to obtain resource sufficiency. The findings also offer an insight into how sustained government spending cuts and a concomitant residual commitment of local authorities to sport are shaping not only TSSOs relationships with the public sector but also with each other. The article discusses the role of sport in the overall function and remit of the TSSOs that comprise the sample as the sector adapts to compliment a 'smarter' state.